Dentro ou fora do eixo: uma cartografia das controvérsias acerca da produção cultural no Brasil - Mariângela Solla Lopez (2014)
Founded in 2005 by four independent collectives from the States of Mato Grosso, Paraná, Acre and Minas Gerais, the Fora do Eixo defines itself as a collaborative and decentralized network, constituted by collectives of culture, which acts based on the principles of solidary economy applied to the productive culture chains, especially the independent music, breaking with the traditional model of the large industry. Throughout its history, the actions of the group always generated many controversies which increased since moving to the city of São Paulo, in 2011. Considering that currently we witness the dilution of solid constructed in the modernity and we live with hybrid phenomena that lead to changes in the way society acts, such as the Fora do Eixo, we seek to map the practices, methods of organization, associations, themes and tensions which circulate and constitute the collective to bring out the network of meanings that is drawn on its surroundings. The thesis focuses on the network notion (SÉRRES,1967; MUSSO, 2010; MARTINHO, 2011) and on the perspective of Actor-Network Theory (LATOUR, 2012), based on the cartography of controversies described by Venturini (2008, 2010, 2012), to reach the translations of the collectives. The results of this study are presented in two parts: in the first, we find a hybrid map constructed with the aim of showing how the Fora do Eixo arises and how it organizes itself, making a report of the network based on its discourse. In the second part, we present a cartography of controversies, describing the facts and presenting the arguments which put into evidence interplay of forces in the field of cultural production in Brazil.